2021
DOI: 10.1007/s12325-021-01801-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of a Bilastine Once-Daily, Preservative-Free, Ophthalmic Formulation

Abstract: Introduction: Bilastine is a second-generation H 1 antihistamine indicated for the symptomatic treatment of allergic rhinoconjunctivitis and urticaria. On the basis of the demonstrated efficacy and safety of the oral formulation, a new ophthalmic formulation of bilastine was recently developed. Previous preclinical studies had indicated that bilastine is mainly absorbed by the conjunctiva and shows low plasma concentration. The objective of this study was to evaluate the pharmacokinetics and safety of ophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The ophthalmic administration of bilastine leads to low absorption into the bloodstream. The median time for maximum plasma concentration attained within 2.5 hrs and half-life in plasma has been reported as 7.88 ± 6.72 hrs 14 . However, a recent experiment on a rabbit model for biodistribution of 0.6% bilastine eye drops showed quantifiable concentrations of bilastine up to 24 hrs in the conjunctiva tissues after installation into the eyes 15 .…”
Section: Properties Of Bilastinementioning
confidence: 99%
“…The ophthalmic administration of bilastine leads to low absorption into the bloodstream. The median time for maximum plasma concentration attained within 2.5 hrs and half-life in plasma has been reported as 7.88 ± 6.72 hrs 14 . However, a recent experiment on a rabbit model for biodistribution of 0.6% bilastine eye drops showed quantifiable concentrations of bilastine up to 24 hrs in the conjunctiva tissues after installation into the eyes 15 .…”
Section: Properties Of Bilastinementioning
confidence: 99%
“…To prepare ten grams of SNEDDS components mixture, the oil concentration was ranged from 15 % to 30 % for each selected Smix. While the concentration of tween 60 and transcutol was calculated according to their ratio (Smix) as shown in table (1). The effects of oil concentration and Smix on the particle size distribution and emulsification time were studied.…”
Section: Formulation Of Bilastine-loaded Sneddsmentioning
confidence: 99%
“…Bilastine (BL) is a new, well tolerated second generation H1-antihistamine. It is indicated for the treatment of chronic spontaneous urticaria and seasonal rhino conjunctivitis (1) . BL is also effective in all nasal symptoms including obstruction and in allergic conjunctivitis (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a once-daily, preservative-free, bilastine ophthalmic formulation has been developed for the specific treatment of allergic conjunctivitis. Pre-clinical in vivo biodistribution and pharmacokinetic studies in humans with this formulation showed that bilastine is predominantly distributed in the conjunctiva, the intended target tissue, while it is poorly absorbed in the blood stream [31,32].…”
Section: Introductionmentioning
confidence: 99%